Computing with subthreshold leakage device/circuit - Raychowdhury, A.
This paper presents a novel design methodology for ultralow-power design using subthreshold leakage as the operating current (suitable for medium frequency of operation: tens to hundreds of millihertz). Standard design techniques suitable for super-threshold design can be used in the subthreshold region. However, in this study, it has been shown that a complete co-design at all levels of hierarchy (device, circuit, and architecture) is necessary to reduce the overall power consumption while achieving acceptable performance (hundreds of millihertz) in the subthreshold regime of operation. Simulation results of co-design on a five-tap finite-impulse-response filter shows ∼2.5× improvement in throughput at iso-power compared to a conventional design.
Keywords: Device-circuit-architecture co-design.; Five-tap finite-impulse-response filter; Power consumption; Pseudo-NMOS logic; Subthreshold leakage; Subthreshold logic; Ultralow-power design; Ultralow-power subthreshold operation